INCOME DIVERSIFICATION AND FINANCIAL STABILITY OF BANKS IN NIGERIA - Oluitan, Roseline; Balogun, Morufat Folake (IJRDO - Journal of Business Management, 2018)
Income diversification is a concept that is gaining wider acceptability mostly by banks in the developing countries. This paper studies the possible application of this concept to banks in Nigeria and examines whether it is potent in ensuring financial stability for the system. The study uses secondary data from 1960 to 2015 to conduct a time series with the aid of error correction model and observes positive and significant relationship between income diversification and financial stability. It postulates that income diversification is good for the system. Key Words – Income Diversification; Financial Stability; Banks; Nigeria.